Biosynthesis of 15-deoxy-Δ(12,14)-PGJ(2) and the ligation of PPARγ - Bell-Parikh, L. Chastine (American Society for Clinical Investigation, 2003)
15-deoxy-Δ(12,14)-PGJ(2) (15d-PGJ(2)) has been identified as an endogenous ligand for PPARγ, inducing adipogenesis in vitro. Additional roles for this molecule in the propagation and resolution of inflammation, ligation of NF-κB, and mediation of apoptosis have been proposed. However, quantitative, physiochemical evidence for the formation of 15d-PGJ(2) in vivo is lacking. We report that 15d-PGJ(2) is detectable using liquid chromatography–mass spectrometry–mass spectrometry at low picomolar concentrations in the medium of 3T3-L1 preadipocytes. However, despite induction of COX-2, production of PGs, including 15d-PGJ(2), does not increase during adipocyte differentiation, a process unaltered by COX inhibition. 15d-PGJ(2) is detectable as a minor product of COX-2 in human urine. However, its biosynthesis is unaltered during or after COX activation in vivo by LPS. Furthermore, the biosynthesis of 15d-PGJ(2) is not augmented in the joint fluid of patients with arthritis, nor is its urinary excretion increased in patients with diabetes or obesity. 15d-PGJ(2) is not the endogenous mediator of PPARγ-dependent adipocyte activation and is unaltered in clinical settings in which PPARγ activation has been implicated.